Russian geological education in the world market (the case of Russian State Geological Prospecting University) - Lisov, V.I. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2016)
Higher geological education in Russia and in MSGPI-RSGPU specific. It - engineering. The mineral deposits determine the development of the global industry and foreign trade. Growing global demand for the profession of geologists and mining engineers. Training of foreign students in Russia has its own geopolitical and economic importance. In Russia a strong resource-based economy. It attracts students from developing countries. MGRI-RSGPU is the leading universities training specialists for mining. The article presents data about the University and types of education. Shown scientific and educational problems in higher education. This article discusses the prospects for the promotion of Russian higher geological education at the world market of educational services. The increasing role of new scientific and technological achievements in mining, enhanced environmental as well as staff requirements is revealed. Given that the leading schools in the mining industry, in addition to Russia, are formed in Canada, Germany, USA, Australia, Great Britain, many developing countries rich in natural resources, have begun to form their own national centers for training in this area. Under such competitive conditions Russian geological education maintains its own niche. Recognition of this is the active participation of Russian universities in the creation and development of the World Forum of sustainable development of mineral universities (WFURS), described in the article. The main factors of competitiveness that led to leading positions of Russian State Geological Prospecting University in system of the Russian geological education are described. Particular attention is paid to the international activities of Russian higher educational institutions including Geological Prospecting University. The basic statistics (both in the context of the country, and in the field) of foreign undergraduate and graduate students enrolled at this university is provided. The article highlights the main problems and prospects of integration of the Russian geological education in the world market of educational services.